Cell permeabilization processes for improved encapsulation of oregano essential oil in yeast cells. (April 2021) - Dimopoulos, George; Katsimichas, Alexandros; Tsimogiannis, Dimitrios; Oreopoulou, Vassiliki; Taoukis, Petros
Abstract: The encapsulation of oregano essential oil in yeast cells was studied. Untreated cells, cells autolyzed for 8 and 24 h at 52 °C, cells treated with Pulsed Electric Fields at three different energy inputs (3.2, 13.6 and 107 kJ/kg) and cells treated with High Pressure Homogenization at 800 bar/4 passes were comparatively assessed. Encapsulation was performed by incubating the cell materials in contact with the oil at temperatures 30, 37, 45 and 65 °C for up to 48 h. Apart from homogenization, none of the other cell pretreatments affected the final encapsulation load at the temperatures studied. All pretreatments had a significant effect on the encapsulation kinetics, leading to increased encapsulation rates compared to the untreated sample. The essential oil release from the obtained capsules was found to depend on water activity and became significant above aw  = 0.7, with cell pretreatments increasing the released oil percentage at higher water activities. Highlights: Oregano essential oil was encapsulated in yeast cells. Autolysis, PEF and HPH were assessed as cell pretreatments. All cell pretreatments accelerated the kinetics of encapsulation. Release of oil from the capsules was significant above aw  = 0.7